Sistema portable para la adquisición y procesamiento de señales ECG, con aplicabilidad en dispositivos móviles (2017)
The acquisition of electrocardiogram (ECG) signals is vital for diagnosing cardiovascular diseases, as it can reveal the actual state and conditions of the heart in patients under study. Currently, the fast advance of the electronic engineering had allowed the development of applications on the biomedicine field, implementing devices that allow bioelectrical signal acquisition and processing, leading to a specific and punctual monitorization of several organs of the human body. This makes easier, faster and better the medical procedures, improving the patients’ conditions during the medical interventions. In this project, a design of a portable system for ECG signal acquisition and processing, with applicability in mobile devices, is proposed, which is characterized principally for being a portable device that is easy to implement, both in the patient’s residences, as well as health care centers. The first step to develop the prototype is to build the electronic board based on the ADS1298 application-specific integrated circuit, by Texas Instruments Company, designed principally for ECG signals that counts with eight channels for data acquisition and a SPI communication port. The board works with the PIC32MX795F512H by the Microchip Company as the main processor of the system, which also has a SPI port for data transference between the ADS1298 and the PIC. The device programming is done through the MPLAB interface programming environment (MPLAB IPE), using libraries that were especially designed for the main code of the proposed device. Finally, a graphical user interface made in MATLAB® was implemented to display the recorded signals. The performed tests to validate the correct functionality of the ECG device shows that the planned development system has been accomplished, both in hardware and software. The needed requirements have been implemented in accordance with international rules of biomedical equipment. Finally, a device that registers twelve leads of ECG (Lead I, Lead II, Lead III, aVF, aVR, aVL, V1, V2, V3, V4, V5 y V6) has been obtained with a sample frequency of 250SPS, which can be visualized and registered in MATLAB®.